1998
DOI: 10.1093/humrep/13.6.1519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of hysterosalpingo contrast sonography in 500 consecutive, unselected, infertile women

Abstract: The performance of hysterosalpingo contrast sonography (Hy Co Sy) as a first-line, outpatient investigation of tubal patency was examined in 500 consecutive, infertile women, at one centre. Hy Co Sy was completed in 463 (92.6%) cases, using a galactose microbubble contrast agent (Echovist-200) and transvaginal sonography. Initial plain scanning identified adnexal pathology in 198 women (39.6%). Examination with Echovist was attempted for 905 tubes and only 67 (7.4%) were not assessable; after the first 100 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
4
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 34 publications
7
34
4
5
Order By: Relevance
“…Despite many patients reporting pain during the procedure, all of the patients reported satisfaction with the procedure. Prior articles documented that the mean times (12 to 13.9 minutes) and the contrast agent doses (5 to 15 ml) for 2 D HyCoSy [5,[20][21][22]. In our research, the longest whole assessment time attained 30 minutes, and the maximum SonoVue dosage arrived at 37 ml, primarily due to lack of experience in the beginning.…”
Section: Discussionmentioning
confidence: 63%
“…Despite many patients reporting pain during the procedure, all of the patients reported satisfaction with the procedure. Prior articles documented that the mean times (12 to 13.9 minutes) and the contrast agent doses (5 to 15 ml) for 2 D HyCoSy [5,[20][21][22]. In our research, the longest whole assessment time attained 30 minutes, and the maximum SonoVue dosage arrived at 37 ml, primarily due to lack of experience in the beginning.…”
Section: Discussionmentioning
confidence: 63%
“…One of its limitations is the rapid degradation requiring the solution to be mixed immediately before infusion, as its ultrasonic hyperechoic characteristics are usually lost within 5 minutes. Given that Echovist-200 is not FDA approved in the United States, other providers have substituted a mixture of saline and air for the distending media (16,(40)(41)(42). Some studies reported vigorously shaking a syringe of saline and air immediately before infusion.…”
Section: Hysterosalpingo-contrast Sonographymentioning
confidence: 99%
“…Some studies reported vigorously shaking a syringe of saline and air immediately before infusion. Alternatively, a syringe filled with both air and saline can be tilted such that an intermittent infusion of air is followed by saline in increments of 1-3 mL at a time (16,(40)(41)(42)(43). More recently, Femasys has achieved US FDA approval for the Femvue Sono Tubal Evaluation System, designed to simultaneously introduce air and saline in a controlled fashion.…”
Section: Hysterosalpingo-contrast Sonographymentioning
confidence: 99%
See 1 more Smart Citation
“…The tube can now be examined directly in real time under magnification and in its natural habitat under physiological conditions contrary to HSG. 22 Exploration of the tube is now more extensive with more dynamic investigative maneuvers and with less risks, incidents and accidents.…”
Section: Endoscopic Evaluationmentioning
confidence: 99%